Analysis Of Effect Of Roadside Parking Space Retribution To Local Own-Source Revenue Of Temanggung Regency - Priska Erlyn Oktaningrum; Selfia Bintariningtyas (Optimum: Jurnal Ekonomi dan Pembangunan, 2021)
This study aims to determine (1) The influence of Roadside Parking Space Retribution to Local Own-source Revenue of Temanggung Regency (2) The potential of Roadside Parking Space Retribution of Temanggung Regency on March 2021 (3) The trend of Roadside Parking Space Retribution of Temanggung Regency on March until May 2021 (4) The effectiveness and efficiency ratio of Roadside Parking Space Retribution revenue of Temanggung Regency on 2017 until 2020. This research uses a descriptive quantitative approach. The secondary data was obtained from the Department of Transportation, consisting of the target data for parking retribution, collection fees and the realization of parking retribution that are used in significance test analysis, potential secondary data, trend analysis, effectiveness analysis and efficiency analysis, while the primary data is obtained directly from interviews with parking attendants to calculate the parking potential of primary data. The results of this study are (1) The Roadside Parking Retribution significantly influenced to Local Own-source Revenue of Temanggung Regency (2) The potential of Roadside Parking Retribution could be developed in order to reach its maximum potential (3) Economic forecasting showed that the next three period downward trend will likely occur (4) The effectiveness ratio of Roadside Parking Retribution revenue categorized as very effective and the efficiency ratio categorized as very efficient. It would be best for Department of Transportation of Temanggung Regency to do an annual survey once a year and to improve awareness on how to use a ticket parking among the people.